Nickel alloys in today's electronics industry - Isleib, C. R. (Nickel Development Institute, 1987)
Nickel-containing alloys have played an important role in electronic components. Nickel and nickel alloy wire and strip have been used extensively in electrical and electronic devices because of these alloys' combination of desirable physical and mechanical properties, including high strength at high and low temperatures, toughness, corrosion resistance, controlled thermal expansion, workability, and excellent spring properties. This publication describes uses of nickel alloys in electronic industries.
"Paper given at the 20th Annual Connectors and Interconnection Technology Symposium, Philadelphia, PA, U.S.A., October 18-21, 1987"
Keywords: Electronics -- Materials.; Nickel alloys.; elektronické knihy; electronic books